Curriculum and Technology Design: A Course to Explore Technology Applications in EFL Curriculum Design - Yuyun, Ignasia (University of Muhammadiyah Prof. DR. HAMKA, 2018)
Teaching and technology pedagogy should be mastered by a teacher in this digital era. It is an inevitable fact that teachers should realize. To be in line with technology development, teachers are expected to bring any technology-based applications to the classroom.  Many education institutions from Kindergarten to Higher Education around the world equip their teachers with technology-based training. In particular, Technology Enhanced Language Learning (TELL) has been mushrooming in English Language Teaching trends. To comply with this demand, Technological Pedagogical and Content Knowledge (TPACK) framework has been developed by Koehler & Mishra (2006) to equip student teachers in English Department. Therefore, Technology and Curriculum Design course is designed to tailor Pre-Service English Teachers how to integrate technology in EFL curriculum design. By having blended learning activities, teaching and learning activities are conducted to explore technology applications to design an EFL curriculum. Any class projects are technology-based assignments such as infographic, poster, mind map, questionnaire, presentation, etc. using CANVA, Google applications, presentation applications, lesson plan application (LessonWRITER), quiz application (Quizlet), and interactive book applications (AnyFlip, Flipping Book, FlipSnack), etc.                Keywords: curriculum, EFL, technology